2013
DOI: 10.1038/ejhg.2013.246
|View full text |Cite
|
Sign up to set email alerts
|

Allele-specific regulation of DISC1 expression by miR-135b-5p

Abstract: Disrupted-in-schizophrenia-1 (DISC1) gene has been established as a risk factor for various neuropsychiatric phenotypes. Both coding and regulatory variants in DISC1 have been identified and associated with these phenotypes in genetic studies. MicroRNAs (miRNAs) are important regulators of protein coding genes. Since the miRNA-mRNA target recognition mechanism is vulnerable to disruption by DNA polymorphisms, we investigated whether polymorphisms in the DISC1 3 0 UTR affect binding of miRNAs and lead to allele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…miRNA-135s target many different tumor-related genes and thereby affect cell proliferation, differentiation, and metastasis formation ( Despite specific expression of miR-135s in the developing and adult nervous system ( Fig. 2; Lagos-Quintana et al, 2001; Sem-pere et al., 2004;Ziats and Rennert, 2014;Caronia-Brown et al, 2016), much less is known about the neuronal functions of miR-135s. miR-135a is required for chronic stress resiliency, antidepressant efficacy, and 5-HT activity in adult mice (Issler et al, Figure 6.…”
Section: Novel Neuronal Functions For Mir-135a and Mir-135bmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNA-135s target many different tumor-related genes and thereby affect cell proliferation, differentiation, and metastasis formation ( Despite specific expression of miR-135s in the developing and adult nervous system ( Fig. 2; Lagos-Quintana et al, 2001; Sem-pere et al., 2004;Ziats and Rennert, 2014;Caronia-Brown et al, 2016), much less is known about the neuronal functions of miR-135s. miR-135a is required for chronic stress resiliency, antidepressant efficacy, and 5-HT activity in adult mice (Issler et al, Figure 6.…”
Section: Novel Neuronal Functions For Mir-135a and Mir-135bmentioning
confidence: 99%
“…Interestingly, miR-135b was the top hit of our image-based miRNA screen for neuronal morphology and subsequent experiments confirmed and extended this observation by revealing that neuronal miR-135b and its homolog miR-135a are required for neurite outgrowth and cortical neuron radial migration in vitro and in vivo. These observations reveal novel functions for miR-135a and miR-135b and are intriguing because miR-135a has been linked to disorders such as epilepsy and schizophrenia, which are characterized by structural changes in neuronal networks (Kan et al, 2012;Rossi et al, 2014;Alsharafi and Xiao, 2015). For example, expression of miR-135a is upregulated in the hippocampus of patients suffering from temporal lobe epilepsy (Kan et al, 2012) and it will be interesting to determine whether, and if so how, this miRNA contributes to pathogenic processes such as mossy fiber sprouting and granule cell dispersion observed during epilepsy.…”
mentioning
confidence: 99%
“…Saetre et al (33) found that the polymorphism of DISC1 in the 3'-UTR enhances susceptibility to SCZ. Rossi et al (17) conducted a functional study and demonstrated that genetic variation in the 3'-UTR of DISC1 increases the gene expression levels and affects SCZ-associated phenotypes by disrupting miRNA-mRNA target recognition. In the present study, the 3'-UTR of the rs2844337 polymorphism of the PAK1 gene was significantly associated with the susceptibility of the Chinese Han population to SCZ.…”
Section: Discussionmentioning
confidence: 99%
“…In human-induced pluripotent stem cells, a rare functional SNP (rs1130354) in the 3'-UTR of the dopamine receptor D2 gene (DRD2) disrupts the targeting of miR-326 to the mRNA of DRD2; as a result, dopamine signaling in patients with SCZ is dysregulated (16). The G allele of the rs11122396 polymorphism, which is located in the 3'-UTR of the DISC1 gene, may be functionally related to the schizophrenic phenotypes of miR-135b-5p; however, this G allele may no longer regulate the mRNA level of DISC1 (17). Furthermore, rs11237200 is located near the 5'-UTR in the 77474957 position of the PAK1 gene.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated polymorphic microRNA binding sites in target genes related to SCZ. These include rs3822674, which is located in the 3ʹ untranslated region (UTR) of the gene encoding complexin II ( CPLX2 ) and is predicted to interfere with repression of CPLX2 expression by miR‐498; rs1130354 in the 3ʹUTR of dopamine receptor D2 gene ( DRD2 ) was reported to interfere with miR‐326‐mediated repression of DRD2 expression; and rs11122396 in the 3ʹ UTR of the disrupted‐in‐schizophrenia‐1 ( DISC1 ) gene disrupted miR‐135b‐5p‐mediated control of DISC1 expression …”
mentioning
confidence: 99%